ANALISI KUALITATIF TRANSPARANSI ANGGARAN PUBLIK DAN DAMPAKNYA TERHADAP OPINI WAJAR TANPA PENGECUALIAN PEMERINTAH DAERAH - Bulu, Yacobin; Susu, Urbaningsi; Kawe, Finsensa; Sel, Yohana; Baso, Susana (Jurnal Pendidikan dan Ekonomi (JUPEK), 2025)
This study was conducted to examine the role of public budget transparency in supporting the achievement of an Unqualified Opinion (WTP) in local government financial reports. Budget transparency is positioned as an important component in creating accountable, efficient governance that is free from malpractice. In the practice of local financial management, the provision of open budget information not only allows the public to access the process of planning, implementation, and reporting of the budget, but also helps improve the accuracy of recording and the quality of financial report presentation. This study uses a descriptive qualitative method through a case study of local governments that have received an unqualified opinion. Data was collected through in-depth interviews, observations on information disclosure, and reviews of regional budget documents and financial reports, then verified through triangulation of sources and methods. The results show that budget transparency has a clear influence on strengthening accountability, increasing the effectiveness of internal control, and maintaining data consistency between regional organizations. Regions that implement information disclosure on an ongoing basis tend to have more organized financial reporting systems, lower material errors, and higher levels of trust from auditors in assessing compliance with Government Accounting Standards. In addition, transparency.